AN ANALYSIS OF USERS’ VIEWS TOWARDS INTERNET BANKING SERVICES PROVIDED BY PUBLIC SECTOR BANKS IN TIRUNELVELI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
A bank is a financial institution that accepts deposits and channels those deposit into lending activities. With the increase in competition, the banks are focusing more on users’ delight through first- class services. The net banking offer allows and users perform a variety of banking features conveniently. To meet this challenge the actual e- banking services provided by a bank needs to support expected functionalities involved in this domain. The present paper critically studies the internet banking outline involving public sector banks in Tirunelveli district.